Implementasi Metoda Sum Squared Error untuk Identifikasi Kategori Pembakaran Mesin Sepeda Motor 4 Tak Bahan Bakar Bensin - Andrizal - -; Rusfandi - -; Rivanol Chadry - (Jurnal Ilmiah Poli Rekayasa, 2016)
Motorcycles with injection system uses engine scanner tool as a reference for a mechanic when performing a tune-up to find out and get the engine firing conditions were perfect. Unlike the motorcycle carburetor system, relying only on the experience of a mechanic. If using tools, usually using exhaust emission analyzer which only serves to measure the levels of elements and compounds and exhaust emissions and it can not be used to identify the condition of the combustion engine. Besides, not all the workshops have it, just a certain manufacturer authorized workshops, garages and a large scale or related government agencies that have it. There are two categories of combustion engine, the first engine combustion conditions are not perfect and complete combustion conditions. Perfect engine combustion conditions is needed so that maximum engine performance with an efficient use of fuel. This study aims to make a device that is capable of detecting the condition of combustion 4-stroke motorcycle carburetor system using the method of sum square error (SSE) through the value of the data patterns of exhaust emissions based gas sensors. The study, of the five categories of motorcycles with the manufacturer, type and year of manufacture of different shows that, the system made capable of identifying categories of combustion engine based on the SSE on the identification and reference set. The success rate of identification detection system performs the complete combustion of 89.33% and 97.99% of incomplete combustion.